Extraction Optimization and Characterization of Gelatin from Half-Smooth Tongue Sole (Cynoglossus semilaevis Gunther) Skin. Issue 6 (3rd July 2019) - Li, Yanjie; Tang, Chunming; He, Qingfeng; Li, Xiaodan; Zhang, Ailin
ABSTRACT: Half-smooth tongue sole is a popular warm-water fish, and its skin may be an available resource for gelatin extraction. Response surface method was used to optimize the extraction of gelatin from the fish skin. The most suitable conditions for maximum gelatin yield (24.2%) were pretreatment with 1.9 g/L NaOH, followed by hot water extraction at 63.54ºC for 4.81 h. The obtained gelatin had a high imino acid content (185 residues/1, 000 residues), with a high content of crude protein and low levels of ash, fat, and moisture. The predominant sodium dodecyl sulfate–polyacrylamide gel electrophoresis bands revealed that the gelatin contained low-molecular-weight peptides, α-, β-, and γ chains. As compared with bovine gelatin, the fish skin gelatin solution had lower values of strength and clarity and higher levels of L* and viscosity. Additionally, Fourier-transform infrared spectra showed that gel from the gelatin had four amide bands (amide A, amide I, amide II, and amide III) similar to commercial gelatin. The results suggest that half-smooth tongue sole skin could be a promising source of gelatin in view of the comparability between its gelatin and commercial gelatin in physicochemical properties.